2016
DOI: 10.2465/jmps.150929
|View full text |Cite
|
Sign up to set email alerts
|

Hadean detrital zircon in the North China Craton

Abstract: Due to a lack of rock samples from the Hadean Eon, the Hadean zircons have become an important means of understanding the Earth's earliest history. This study reports the occurrence of a Hadean detrital zircon with a concordia U-Pb age of 4081 ± 71 Ma and 207 Pb/ 206 Pb age of 4087 ± 31 Ma from the Paleoproterozoic metasedimentary rocks in the Jiao-Liao-Ji Belt (JLJB) in the North China Craton. The analyzed zircon grain exhibits low luminescence and striped absorption and has relatively high Th/U ratio (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Jin, ; Wu, Zhang, Yang, Xie, & Yang, ; Zhu et al, ). The latest zircon data indicate that the North China craton potentially contains even a Hadean crust in its northeastern part (Z. Li, Chen, & Wei, ); however, no Neoproterozoic granitoids occur. In contrast, the South China block is characterized by dominantly Proterozoic crust, with minor components of Archean crust (Lei & Shu, ; H. L. Li et al, ; Su et al, ; Zhao et al, ).…”
Section: Precambrian Zirconsmentioning
confidence: 99%
“…Jin, ; Wu, Zhang, Yang, Xie, & Yang, ; Zhu et al, ). The latest zircon data indicate that the North China craton potentially contains even a Hadean crust in its northeastern part (Z. Li, Chen, & Wei, ); however, no Neoproterozoic granitoids occur. In contrast, the South China block is characterized by dominantly Proterozoic crust, with minor components of Archean crust (Lei & Shu, ; H. L. Li et al, ; Su et al, ; Zhao et al, ).…”
Section: Precambrian Zirconsmentioning
confidence: 99%
“…The active continental margin tectonic model, first proposed by Bai et al [33], posits that the LB and LNB represent two exotic blocks while the JLJB is an intervening island arc or back-arc basin. This viewpoint has been supported by various pieces of evidence, including: (1) studies of Paleoproterozoic Liao-Ji granites using geochronology and geochemistry, which revealed that the I-and A2-type ~2.2-2.0 Ga granites constituted a calc-alkaline series likely formed in the extensional tectonic setting of a continental arc [52,54,55,120] and/or back-arc basin [27,38,90,106,[121][122][123]; (2) the reinterpretation of previously regarded (meta-)mafic rocks, which were believed to be examples of bimodal magmatism, together with the meta-volcanic rocks and Liao-Ji granites, that were developed in a rift environment as typical island arc basalts formed in a back-arc tectonic setting [15,24,68,124]; and (3) newly obtained detrital zircon U-Pb ages, combined with previous studies [27,104], showing unimodal age peaks of ~2.5 Ga for the Langzishan Fm. and ~2.15 Ga for the Li'eryu Fm., and bimodal age peaks at ~2.51 Ga and ~2.17 Ga for the Gaojiayu and Dashiqiao formations, respectively.…”
Section: Geological Significance and Sedimentary Backgroundmentioning
confidence: 95%
“…In around 2.2-2.0 Ga, a back-arc basin was initially formed. Accompanied by lithospheric extension and mantle upwelling, the partial melting of ancient crustal material, together with minor contributions of juvenile mafic rocks, generated widespread A2-type granitoids in the JLJB [27,[54][55]90,[120][121][122][123]. During this time, a large volume of volcanic clastics (boron-bearing), and debris derived from the magmatic arc, were rapidly deposited, forming the Li'eryu Fm.…”
Section: Geological Significance and Sedimentary Backgroundmentioning
confidence: 99%
“…The abundant occurrence of Hadean detrital zircon is limited in ca. 3.0-3.3 Ga sandstone and quartzose clastic rocks (Froude et al, 1983;Compston and Pidgeon, 1986;Wilde et al, 2001;Cavosie et al, 2007;Nebel et al, 2014;Valley et al, 2014;Nelson, 2002;Wyche et al, 2004;GSWA;2005;Wyche, 2007;Paquette et al, 2015;Byerly et al, 2018), even though many odd localities have been reported (Mojzsis and Harrison, 2002;Iizuka et al, 2006;Martel et al, 2008;Diwu et al, 2013;Nadeau et al, 2013;Cui et al, 2013;Xing et al, 2014;Li et al, 2016).…”
mentioning
confidence: 99%